Age and rate of diversification of the Hawaiian silversword alliance (Compositae) - Baldwin, Bruce G. (The National Academy of Sciences, 1998)
Comparisons between insular and continental radiations have been hindered by a lack of reliable estimates of absolute diversification rates in island lineages. We took advantage of rate-constant rDNA sequence evolution and an “external” calibration using paleoclimatic and fossil data to determine the maximum age and minimum diversification rate of the Hawaiian silversword alliance (Compositae), a textbook example of insular adaptive radiation in plants. Our maximum-age estimate of 5.2 ± 0.8 million years ago for the most recent common ancestor of the silversword alliance is much younger than ages calculated by other means for the Hawaiian drosophilids, lobelioids, and honeycreepers and falls approximately within the history of the modern high islands (≤5.1 ± 0.2 million years ago). By using a statistically efficient estimator that reduces error variance by incorporating clock-based estimates of divergence times, a minimum diversification rate for the silversword alliance was estimated to be 0.56 ± 0.17 species per million years. This exceeds average rates of more ancient continental radiations and is comparable to peak rates in taxa with sufficiently rich fossil records that changes in diversification rate can be reconstructed.